Analisis Tindak Pidana Penggelapan Berkedok Cash Tempo Dalam Kepemilikan Fasilitas Kredit Pemilikan Rumah (KPR) - Arcaropeboka, Rj. Agung Kesuma; Saputra, Aris Hadi; Yunus, Muh (Universitas Sang Bumi Ruwa Jurai, 2024)
There are many ways that people can take to meet their basic housing needs. This is where banks appear to bridge the interests of home buyers and sellers by offering home ownership credit facilities. Based on this, many parties, even housing developers (developers) are trying to take advantage of this problem by dealing with house sales without going through the bank mortgage process but instead diverting it using cash due payment, namely the payment process in installments directly to the developer as the developer at the same time. as a provider of housing funds. The aim of this research is to explain how to prove criminal acts of embezzlement under the guise of cash tempo and how the judge's legal considerations are regarding perpetrators of criminal acts of embezzlement under the guise of cash tempo. This research uses a normative juridical and empirical juridical approach, using types of secondary data and primary data. Data analysis was carried out using qualitative analysis. The results of the research showed that proof of the crime of embezzlement under the guise of cash tempo was carried out by taking into account the evidence presented at the trial conducted by the prosecutor by presenting 4 (four) witnesses, documentary evidence and the defendant's statement which explained that the defendant had committed the crime of embezzlement. under the guise of cash due. The conclusion in this research is that there is a difference in the judge's decision and the prosecutor's demands, where the defendant's claim is that he was found guilty of violating Article 372 of the Criminal Code with a prison sentence of one year and six months minus the time the defendant was in detention (temporary). Meanwhile, the judge sentenced the defendant to imprisonment for one year and three months.